A Multiple-community Overlap Measure Based on a Probabilistic Approach. Issue 4 (20th April 2016) - Yue, Jack C.; Clayton, Murray K.
Abstract : Species diversity indices are designed to measure the species diversity of a community and to compare the species distribution structure of two communities. The Shannon and Simpson indices are for describing one community, and the Jaccard and Morisita indices are for comparing two communities. Only a few indices allow the simultaneous comparison of three or more communities. In this study, we propose a multiple-community similarity index based on a probabilistic approach, and compare it with other multiple-community indices. Empirical examples are considered as a demonstration of the proposed similarity indices.